PTU-328 Colonic evaluation after acute diverticulitis – is it time for a change in practice?. (22nd June 2015) - Shahid, S; Nana, G; Huang, A; Gorard, D
Abstract : Introduction: UK commissioning guidelines recommend colonic evaluation after an attack of acute diverticulitis to exclude colorectal malignancy. However, recent studies demonstrate increased accuracy of Computed Tomography (CT) in diagnosing acute diverticulitis and suggest a selective approach to further colonic evaluation in cases of complicated acute diverticulitis. Therefore, the role of routine colonic luminal imaging following CT proven acute diverticulitis is debatable. Our aim was to audit colonic evaluation following CT diagnosis of acute diverticulitis over a 12 month period and review the requirement for this as a routine follow-up investigation. Method: A two part audit in a district hospital. Firstly, all patients admitted with CT-proven acute diverticulitis from 1 st Jan 2013 to 31 st Dec 2013 were followed up for the results of colonic evaluation by endoscopy, CT colonography or CT Long prep. Secondly all patients discussed in the lower gastro-intestinal tract multi-disciplinary meeting (LGI MDT) over the same 12 month period had a retrospective review of imaging for a CT diagnosis of acute diverticulitis in the preceding 12 months. Results: 101 patients (mean age 67 yrs) had acute diverticulitis (57 uncomplicated and 34 complicated) confirmed on CT. 43 patients underwent further colonic evaluation (30 in uncomplicated diverticulitis yielding one cancer). No cancers were found in the complicated diverticulitis group. Of 191 patient discussed in the LGI MDT, 63 had a CT scan preceding a lower GI endoscopy (33%). 2 of these had an in-patient CT scan for clinically suspected acute diverticulitis. One patient had sigmoid diverticulosis (but no inflammation) and an incidental finding of a caecal tumour. The second had acute uncomplicated sigmoid diverticulitis but a co-existent malignancy could not be excluded (further investigation confirmed a sigmoid tumour). Conclusion: Less than half the patients admitted with acute diverticulitis at our centre underwent subsequent investigation of the colonic lumen and only one cancer was detected. Despite the low referral rate for follow-up colonic imaging, cross referencing with our cancer data base shows our radiologists are accurate in diagnosing acute diverticulitis on CT and that masquerading cancers are rare. Disclosure of interest: None Declared.